Penerapan Penilaian Berbasis Kelas di SDN Pondok Jagung 01 Kota Tangerang Selatan - Ina Magdalena; Noer Khotijah Faizha; Nendeen Dhias Galera; Rani Komalasari; Hana Afifah (RC-INSTITUT, 2020)
The purpose of this journal is to describe the application of classroom-based assessment at SDN Pondok Jagung 01 Kota Tangerang Selatan. This research uses a descriptive qualitative approach through interviews and document analysis. The results of this study indicate that SDN Pondok Jagung 01 Kota Tangerang Selatan has designed and implemented classroom-based assessment in accordance with applicable guidelines.